2018
DOI: 10.1017/s0263574718001236
|View full text |Cite
|
Sign up to set email alerts
|

RimJump: Edge-based Shortest Path Planning for a 2D Map

Abstract: SummaryPath planning under 2D map is a key issue in robot applications. However, most related algorithms rely on point-by-point traversal. This causes them usually cannot find the strict shortest path, and their time cost increases dramatically as the map scale increases. So we proposed RimJump to solve the above problem, and it is a new path planning method that generates the strict shortest path for a 2D map. RimJump selects points on the edge of barriers to form the strict shortest path. Simulation and expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In the study of the GWO algorithm, path planning found that the path is affected by the number of path node, path node generally set for developers, violates the principle of the shortest distance between two points, the fitness function value is affected by the path node number at the same time, generally will increase the final optimization results of the algorithm. Zhuo et al (2018) use RimJump to decrease the number of path node in A* and Dijkstra algorithm, which inspire us [45].…”
Section: Algorithmmentioning
confidence: 99%
“…In the study of the GWO algorithm, path planning found that the path is affected by the number of path node, path node generally set for developers, violates the principle of the shortest distance between two points, the fitness function value is affected by the path node number at the same time, generally will increase the final optimization results of the algorithm. Zhuo et al (2018) use RimJump to decrease the number of path node in A* and Dijkstra algorithm, which inspire us [45].…”
Section: Algorithmmentioning
confidence: 99%
“…The major difference between the tangent graph and the visibility graph is that the tangent graph can be applied to obstacles with arbitrary boundaries. Then, we proposed a series of tangent graphbased path planning method [10,11] which search the global shortest path in form of path tree instead of a queue, which is always used by general path planning. These approaches can always find the shortest path, and the time cost is insensitive to the map scale increase.…”
Section: @Qqcommentioning
confidence: 99%
“…1. The available range ( [10], [11]) that limit the orientation of tangent during tangent graph searching; 2. Remove paths that contain tangents which cross static or dynamic obstacles; 3.…”
Section: B Path Planning With Distinctive Topologiesmentioning
confidence: 99%
“…The major difference between the tangent graph and the visibility graph is that the tangent graph can be applied to curved obstacles. Then, we proposed a tangent graph based on a 2D path planning method [35,34] using a path tree to search the graph instead of a graph search. The approach can always find the shortest path, and the time cost is insensitive to the map scale increasing.…”
Section: Introductionmentioning
confidence: 99%